2008
DOI: 10.1007/s11605-008-0540-9
|View full text |Cite
|
Sign up to set email alerts
|

Interval Period Tumor Progression: Does Delayed Hepatectomy Detect Occult Metastases in Synchronous Colorectal Liver Metastases?

Abstract: Tumor progression was recognized and occult metastases were detected after the interval reevaluation. Delayed hepatectomy may be a useful approach to reduce rapid remnant liver recurrence in synchronous CRLM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 32 publications
0
28
0
1
Order By: Relevance
“…In particular, rapid growth of preexisting metastatic cancer in the liver after resection of the primary colorectal tumor has been noted by several investigators [6,[50][51][52] . Of note, in one investigation the vascular density of metastases has been noted to be significantly increased over the pre-resection baseline several months after primary resection; this suggests that tumor angiogenesis is stimulated after surgery [53] .…”
Section: Discussionmentioning
confidence: 97%
“…In particular, rapid growth of preexisting metastatic cancer in the liver after resection of the primary colorectal tumor has been noted by several investigators [6,[50][51][52] . Of note, in one investigation the vascular density of metastases has been noted to be significantly increased over the pre-resection baseline several months after primary resection; this suggests that tumor angiogenesis is stimulated after surgery [53] .…”
Section: Discussionmentioning
confidence: 97%
“…A similar surgical outcome has been reported after simultaneous and delayed (or interval) resection of liver metastases, so simultaneous resection has gained acceptance at some institutions [12][13][14][15][16]. However, several authors have recommended a 'test of time' to assess tumor progression [17][18][19][20] on the basis that delaying the resection of apparently resectable synchronous hepatic metastases for 3-6 months might allow occult disease to become detectable; thus, patients who develop unresectable disease during the interval can be spared from undergoing unnecessary surgery.…”
Section: Introductionmentioning
confidence: 74%
“…The optimal surgical strategy for resectable synchronous LM still remains controversial [12][13][14][15][16][17][18][19][20]. Some authors have proposed a ''test-of-time'' approach to assess the biological behavior of the tumor, identify potential occult disease, and avoid surgery in patients with rapidly progressive cancer [17][18][19][20]. Scheele et al [24] reported a poor prognosis of patients with synchronous metastases, and they attributed some of the blame for the poor outcome to failure to remove hepatic micrometastases in patients undergoing resection of overt liver metastases as part of the primary procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, these patients may benefit from neoadjuvant chemotherapy, although there are no data to support this approach. Some advocate a delay in liver resection to allow the biological behavior of the tumor to become evident [83]. No difference in survival outcome was seen in a retrospective review of 73 patients who were either operated on immediately or given a period of observation, although that study was not likely to have detected modest-sized effects [84].…”
Section: What Is the Optimal Timing Of Liver Resection?mentioning
confidence: 99%